COVID-19 Outbreak Can Change the Job Burnout in Health Care Professionals - Liu, Xinghuang; Chen, Jie; Wang, Dongke; Li, Xin; Wang, Erchuan; Jin, Yu; Ma, Yanling; Yu, Cheng; Luo, Chang; Zhang, Lei; Liu, Chuang; Zhou, Yangshiyu; et al. (Frontiers in Psychiatry, 2020)
Background: The outbreak of COVID-19 in China was a sudden bio-disaster, which may bring negative impact on the job burnout of health care professionals (HCPs). Objective: We aim to find out the association factors, especially those closely related to this outbreak, of job burnout in Chinese HCPs. Method: The cross-sectional survey about HCPs’ job burnout based on a network platform was conducted in high and low infection regions of during the COVID-19 outbreak in China. The demographic characteristics, medical-work related factors, risk of getting infected due to occupational exposure and family factor were collected by self-reported questionnaire. The Chinese version of Maslach Burnout Inventory (CMBI) and the Trait Coping Style Questionnaire (TCSQ) were employed in this study to evaluate the job burnout and coping style, respectively. Further, statistical analysis was done to find out the associated factors of job burnout. Results: We collected 880 complete questionnaires from doctors and nurses from February 9, 2020 to February 11, 2020. In this study, the positive rate of three dimensions of burnout (emotional exhaustion, depersonalization, and reduce personal accomplishment) and overall burnout were 9.09%, 50.57%, 56.59% and 73.98%, respectively. After statistical analysis, we found that several factors can independently affect the dimensions. Working in the high infection region and negative coping styles can affect all three dimensions at once. More night shift quantity and having symptoms could increase emotional exhaustion and depersonalization, while higher work intensity and senior could increase emotional exhaustion and reduce personal accomplishment, respectively. Conclusion: The rate of moderate and severe burnout had increased due to the outbreak. More attention should be paid to burnout in HCPs, especially those with negative coping. There are some potential ways to reduce burnout, such as reducing their workload and providing better protection from the virus.